Dynamo in tesla turbine, based on recyclable materials, for decentralized energy generation and recharge batteries: system evaluations - D’ercole, Alessandro de Freitas; Silva, Gabriel Tessarin Menin; dos Santos, João Guilherme Barbosa; Carvalho, Eduarda Regina (Latin American Journal of Energy Research, 2022)
Nowadays the search for new forms of energy generation is one of the great challenges of humanity. Decentralized energy production as well as material recycling, in order to obtain low-cost environmental gains, are extremely important points, as they are issues that must be evaluated in parallel with sustainable development, being extremely discussed and disseminated for their relevance and importance, since the main focus certainly corresponds the environmental preservation of the planet. In view of this theme, in the present work, a prototype was built using Tesla turbine and a dynamo couplet, aiming at the decentralized energy generation model, for the recharge of lead-acid batteries concomitantly with the challenge of reaching an innovative and unprecedented device with economic and environmental gains. The developed system was made and structured from the manufacture of various accessories obtained from recyclable materials attached to its structure, through the improvement of the physical model during its manufacture until the performance of experimental tests investigating its functionality. The results show that the projected system responded significantly to what was proposed, where the dynamo generated current for the system, providing 12 V in the physical model, recharging the battery. In view of the results obtained, it is believed that the prototype has great potential, in a characteristic line and direction, where with the improvement of the structure and diversification of components it is possible to become a new proposal, that is, an innovative device that meets expectations at an affordable price, being a decentralized model of energy generation and environmentally friendly.